Fused teeth in the primary dentition: clinical case report - Amanda Carolina COSTA; Bárbara Salles do NASCIMENTO; Jéssica Luciana Cruz SILVA; Alice Machado Carvalho SANTOS; Suzana Coulaud da Costa CRUZ; Maria Luiza da Matta Felisberto FERNANDES (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Fused teeth are a developmental anomaly involving the union of two dental germs at the crown, root or pulp. This type of anomaly occurs during intraosseous development, resulting in a morphologically irregular tooth that can affect both the primary and permanent dentition. Clinical problems involving esthetics, a lack of space and greater susceptibility to caries are often associated with fused teeth. This type of anomaly is easily confused with dental twinning, which has similar clinical features but emerges from a single dental germ. The aim of the present study was to report a clinical case of the fusion of two deciduous mandibular incisors, describe prospects for treating this anomaly and discuss its repercussions during the development of the dentition. Extraction of the fused tooth was performed and orthodontic treatment was recommended for esthetic and functional improvements. Integrated planning involving both Pediatric Dentistry and Orthodontics provided a better treatment option.